THE ACCOUNTANT AND CHANGING MONETARY VALUES. - Castenholz, William B. (The Accounting Review, 1931)
In approaching the problem of changes in monetary values of fixed assets and what the accountant's attitude should be thereto, it must be considered as affecting both the profit-and-loss statement and the balance sheet. That leads one, at once, into a very fundamental question, what is it that the accountant wants to show in the statement of profit and loss and in the balance sheet, or, what should he show, in these statements, when he is faced with the fact that properties used for the production and sale of commodities are worth more, or less, in terms of price, than the values indicated by the fixed asset accounts? To say, as some do, that the accountant should entirely ignore changes in monetary value, is the equivalent of saying that the tide rises, but the extent of its rise is of no consequence to anybody. Monetary values do change, and they are of consequence. Their consequences should be recognized, measured and expressed, because business is conducted in terms of present monetary values. There is no other way for business to express itself. Yet the orthodox accountant wants business transactions expressed in terms of both past and present monetary values, and he believes that net worth, at any time, can also be properly expressed in such variable terms.